'So very unequal to the place'? The Legal Apprenticeship of John Williams, Lord Keeper, c. 1605–16211. Issue 2 (7th June 2017) - Nicholls, Andrew D.
Abstract: In the spring of 1621, James I sent the Great Seal of England to his newly appointed Lord Keeper, John Williams, the Dean of Westminster. Naming an ecclesiastic to this position shocked contemporary legal and political commentators, and subsequent historians have generally shared this negative appraisal. Even more positive analyses have held that Williams' primary attraction for the king lay in his intellect and learning, and an expectation that he would do James' bidding on the Court of Chancery. Williams actually possessed both stronger legal qualifications than have traditionally been recognized, and a politico-legal philosophy that had helped to modify James' own views of the role of his prerogative courts and powers. An examination of Williams' career prior to 1621 reveals the development of a candidate uniquely placed to fill this particular role at that specific moment in James' reign.